Pharmacokinetics study of atracurium, dexmedetomidine, midazolam and 1-hydroxymidazolam in patients undergoing acute aortic dissection surgery - Si, Huiling; Xu, Xuanxuan; Liang, Yuhao; Shi, Shuaibo; Xie, Fan; Hu, Jie (Frontiers in Pharmacology, 2024)
Objective An UPLC-MS/MS method was developed and validated for simultaneous determination of atracurium (ATC), dexmedetomidine (DEX), midazolam (MDZ) and 1-hydroxymidazolam (1-OH-MDZ) and the pharmacokinetics of ATC, DEX, MDZ and 1-OH-MDZ in patients undergoing aortic dissection surgery were investigated. Methods The analytes were extracted by acetonitrile precipitation and separated on an Acquity UPLC BEH C18 column (2.1 mm × 50 mm, 1.7 μm) with a mobile phase of acetonitrile-0.1% formic acid and a gradient mode. In the positive ion mode, the following mass transition pairs were monitored by multiple reaction monitoring (MRM) for the four analytes and IS: m/z 385.1→206.2 for ATC, m/z 201.2→95.1 for DEX, m/z 326.1→291.1 for MDZ, m/z 341.9→324.0 for 1-OH-MDZ, and 284.9→153.9 for diazepam (IS). Seven male patients undergoing aortic dissection surgery received general anesthesia and intravenous administration of ATC, DEX, and MDZ during the surgery. Venous blood was collected at different time points at the end of surgery and after surgery. The concentrations of ATC, DEX, MDZ, and 1-OH-MDZ were detected, and the pharmacokinetic parameters were calculated. Results The method showed good linearity for each analyte. The inter-batch precision ranged from 1.37% to 9.87% and the intra-batch precision ranged from 2.41% to 10.72%; the accuracy ranged from 94.33% to 104.51%. Finally, the matrix effect, extraction recovery and stability data met the FDA recommended acceptance criteria for validation of bioanalytical methods. The t1/2 of ATC, DEX, MDZ and 1-OH-MDZ was (6.74 ± 2.27) h, (9.55 ± 4.93) h, (10.17 ± 5.35) h, and (6.90 ± 2.38) h, the Cmax, of ATC, DEX, MDZ and 1-OH-MDZ was (1054.20 ± 202.37) ng/mL, (1.93 ± 1.07) ng/mL, (1256.57 ± 389.09) ng/mL, and (1034.39 ± 292.92) ng/mL in patients undergoing aortic dissection surgery, respectively. Conclusion The developed UPLC-MS/MS method for simultaneous determination of ATC, DEX, MDZ and 1-OH-MDZ in patient plasma was accurate, reproducible, specific. After continuous administration of ATC, DEX, and MDZ to patients undergoing surgery for acute aortic dissection, the pharmacokinetics of ATC, DEX, MDZ and 1-OH-MDZ in patients undergoing aortic dissection surgery were studied.